2012
DOI: 10.1080/08952841.2012.638873
|View full text |Cite
|
Sign up to set email alerts
|

“Yes, I worry about my weight … but for the most part I'm content with my body”: Older Women's Body Dissatisfaction Alongside Contentment

Abstract: The majority of body image research has studied younger women and girls, ignoring older age groups. Therefore, the purpose of this study was to explore body image among retirement-age women. The sample included 13 women aged 60 to 69. Data collection occurred in two phases. Participants completed individual in-depth interviews and attended follow-up focus groups. Transcripts from both phases of data collection were analyzed thematically using the constant comparison method. Themes emerged regarding the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 34 publications
4
32
0
1
Order By: Relevance
“…In an interview study of 95 women aged between 20 and 69 years, Montemurro and Gillen (2012) found that the older women were more dissatisfied with their appearance and bodies when evaluated in a sexual or intimate relationship context than in general. In a focus group study (Liechty, 2012), 13 older women (60-69 years) reported that they perceived their bodies more negatively when naked than when clothed.…”
mentioning
confidence: 99%
“…In an interview study of 95 women aged between 20 and 69 years, Montemurro and Gillen (2012) found that the older women were more dissatisfied with their appearance and bodies when evaluated in a sexual or intimate relationship context than in general. In a focus group study (Liechty, 2012), 13 older women (60-69 years) reported that they perceived their bodies more negatively when naked than when clothed.…”
mentioning
confidence: 99%
“…One factor that has been consistently linked to positive body image is the prioritization of function over appearance. For example, age has been related to greater body satisfaction and researchers have suggested that this is due, at least in part, to increased focus on health and physical ability rather than appearance (Liechty, 2012).…”
Section: Positive Body Imagementioning
confidence: 99%
“…Research has also identified sexual orientation as a predictor of positive body image (Morrison, Morrison, & Sager, 2004;Peplau et al, 2009), as lesbians are less likely to internalize societal ideals and may prefer a larger body ideal than heterosexual women (Markey & Markey, 2014). Overall, positive body image has been linked to avoidance of social comparison which allows women to focus on perceived assets rather than uncontrollable aspects of appearance (Liechty, 2012).…”
Section: Positive Body Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Isto favorece a rejeição às pressões e expectativas sociais e uma visão do climatério como um tempo de liberdade (Liechty, 2012;Paquette, Raine, 2004). Recomenda-se uma abordagem assistencial na qual os profissionais de saúde possam abordar conteúdos que expressem a cidadania e equivalência entre as pessoas, mediante suas diferenças e singularidades, inserindo no imaginário coletivo representações positivas sobre o climatério e o processo de envelhecimento (Mendonça, 2011).…”
Section: Discussão 170unclassified